2007
DOI: 10.2170/physiolsci.rp013107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intracellular Ca2+ Transient by the Hybrid Logistic Function in Aequorin-Injected Rabbit and Mouse Papillary Muscles

Abstract: Myocardial intracellular calcium (Ca 2+ ) transients (CaTs) regulate tension generation and relaxation. Isometric tension curves are often analyzed using exponential equations; however, we previously demonstrated that hybrid logistic (HL) functions, which describe the difference between two S-shaped logistic functions, provide more accurate representations. In the present study, we investigated the potential application of HL functions for analyzing CaTs directly. CaTs were measured using the calcium-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In a previous study, we reported that the logistic function curve-fits well the ascending phase from twitch stimulation to the peak Ca 2? concentration [7]. A computer simulation of the CaT also provided a characterization of the logistic function [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we reported that the logistic function curve-fits well the ascending phase from twitch stimulation to the peak Ca 2? concentration [7]. A computer simulation of the CaT also provided a characterization of the logistic function [17].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental procedures have been previously described in detail [4,6,7]. In short, seven albino rabbits (Japan White; body weight 2.0-2.5 kg) and 15 mice (C57BL/6; body weight 25-30 g) were anesthetized with intravenous (1.5-2.0 mg/kg) and intraperitoneal (15-20 mg/kg) pentobarbital sodium, respectively.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…39) We speculate that the tension waveform in Phase I is mainly related to the contraction process; that is, the rapid increase in intracellular Ca 2+ concentration due to Ca 2+ inflow into the cytoplasm, Ca 2+ -induced Ca 2+ release from the SR, Ca 2+ binding to troponin C, and cross-bridge association. 5,7) Conversely, the tension waveform in Phase IV is mainly related to the relaxation process; that is, the decrease in intracellular Ca 2+ concentration due to Ca 2+ dissociation from troponin C and Ca 2+ removal from the cytoplasm, and cross-bridge dissociation.…”
Section: +mentioning
confidence: 99%
“…1,2) Nonlinear regression and curve-fitting may contribute to resolution of the mechanism, summarize information, remove noise, allow speculation regarding unmeasured data, and separate the effects of multiple factors. In an effort to maximize the amount of useful information that can be extracted from the waveforms of the tension and LV pressure curves, these curves have been studied by curve-fitting with mathematical models including sinusoidal, 3) polynomial-exponential, 4) hybrid-logistic, [5][6][7][8][9][10] and hybridWeibull functions. 11) Many attempts have also been made to derive reliable lusitropic indices from the minimum of the first order time derivative of LV pressure (dP/dt min ).…”
mentioning
confidence: 99%